Building Social Empathy Through Orphanage Assistance Activities Bumi Ayu Village - Latip Latip; Lili Suryani; Ninda Oktaviani Putri; Hannisa Effendi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Stunting is a persistent nutritional problem in Indonesia, especially among children under five, affecting the nation's human resource potential. The high prevalence of stunting leads to long-term issues in cognitive development, physical growth, and the overall productivity of the younger generation (Ministry of Health, 2023). This community service initiative seeks to enhance the role of public administration in promoting policies and programs aimed at reducing stunting. It involves education, training, and hands-on community support, coordinated with government officials, health cadres, and local leaders. The initiative utilizes local media to increase awareness about proper nutrition. The results show a noticeable improvement in community knowledge about stunting and balanced nutrition, with both officials and residents actively participating in stunting reduction efforts. This service emphasizes the importance of strengthening public administration through capacity-building, intersectoral coordination, and the use of information technology to meet program objectives. Recommendations are made for sustainable, participatory, and data-driven approaches to stunting reduction.